High hospital readmission rates for patients aged ≥65 years associated with low socioeconomic status in a Swedish region: a cross-sectional study in primary care - Jacques Shebehe; Anders Hansson (Taylor & Francis Group, 2018)
Objective: There is a presumption that hospital readmission rates amongst persons aged ≥65 years are mainly dependent on the quality of care. In this study, our primary aim was to explore the association between 30-day hospital readmission for patients aged ≥65 years and socioeconomic characteristics of the studied population. A secondary aim was to explore the association between self-reported lack of strategies for working with older patients at primary health care centres and early readmission. Design: A cross-sectional ecological study and an online questionnaire sent to the heads of the primary health care centres. We performed correlation and regression analyses. Setting and subjects: Register data of 283,063 patients in 29 primary health care centres in the Region Örebro County (Sweden) in 2014. Main outcome measure: Thirty-day hospital readmission rates for patients aged ≥65 years. Covariates were socioeconomic characteristics among patients registered at the primary health care centre and eldercare workload. Results: Early hospital readmission was found to be associated with low socioeconomic status of the studied population: proportion foreign-born (r = 0.74; p < 0.001), proportion unemployed (r = 0.73; p < 0.001), Care Need Index (r = 0.74; p < 0.001), sick leave rate (r = 0.51; p < 0.01) and average income (r = −0.40; p = 0.03). The proportion of unemployed alone could explain up to 71.4% of the variability in hospital readmission (p < 0.001). Primary health care centres reporting lack of strategies to prevent readmissions in older patients did not have higher hospital readmission rates than those reporting they had such strategies. Conclusion: Primary health care centres localized in neighbourhoods with low socioeconomic status had higher rates of hospital readmission for patients aged ≥65. Interventions aimed at reducing hospital readmissions for older patients should also consider socioeconomic disparities.Key Points In Sweden, hospital readmission within 30 days among patients aged ≥65 has been used as a measure of quality of primary care for the elderly. However, in our study, elderly 30-day readmission was associated with low neighbourhood socioeconomic status. A simple survey in one Swedish region showed that the primary health care centres that lacked active strategies for working with aged patients did not have higher hospital readmission rates than those that reported having strategies. Interventions aimed at reducing elderly hospital readmissions should therefore also consider the socioeconomic disparities in the elderly.